Transforming the nature and delivery of mathematics and science secondary teacher education in Queensland : final report. - Dawes, Les; Loughlin, Wendy; Whitehouse, Hilary; Adams, Peter; Diezmann, Carmel; Nugent, Melissa; Whiteford, Chrystal; Mascadri, Julia (Dept of Education and Training Australia, 2017)
This is the final report from the Step Up project. The Step Up project operated from late 2013 to early 2017 and was funded through the Enhancing the Training of Mathematics and Science Teachers (ETMST) Program. The ETMST Program was a response to the 2012 challenge by the Chief Scientist of Australia for improvements in the preparation of mathematics and science teachers. ETMST identified a complex and multifaceted challenge based around the notion of combining content and pedagogy so that mathematics and science are taught more like they are practised. The project was led by Queensland University of Technology in partnership with Australian Catholic University, Griffith University, James Cook University, The University of Queensland and the Queensland Department of Education and Training. The grant's focus was on pre-service, secondary mathematics and science teachers in Queensland. Step Up sought to identify where significant change and impact can be made – going beyond traditional approaches that have involved providing more content, method and resources, and reconceiving what is possible through collaboration between practising scientists, mathematicians and teacher educators – to prepare the next generation of our nation's science and mathematics teachers.